Pelatihan Internet of Things Berbasis Embedded System untuk Meningkatkan Kompetensi Penelitian Mahasiswa Teknologi Informasi - Yuwaldi Away; Andri Novandri; Isyatur Raziah (Yayasan Kawanad, 2026)
The rapid advancement of Internet of Things (IoT) technology requires Information Technology students to go beyond theoretical understanding and develop hands-on technical skills in building functional real-world systems. This community service activity aims to strengthen students' research competence through integrated training on Embedded Systems and IoT. The implementation approach encompasses theoretical instruction on foundational concepts, hardware familiarization, and direct practice in programming and system integration. Training materials cover the use of the ESP8266 microcontroller, temperature and humidity sensors (DHT22), voltage and current sensors (INA219), the Node-RED platform, and Cloud Server-based databases. Data transmission was carried out using an internet-based communication protocol, while Node-RED served as the primary platform for data flow management and real-time dashboard visualization. The outcomes demonstrate measurable improvement in participants' ability to design remote monitoring systems, perform real-time data visualization, and apply datalogging techniques. These competencies are expected to support the quality of undergraduate final research projects and technology-based innovation initiatives relevant to current societal needs.